Supplementary material to: "Lu Xun on display: memory, space and media in the making of world literary heritage or the materiality of world literary heritage: memory, space and media in the making of Lu Xun" - Graf, Emily (Universität, 2023)
This is the supplementary material to my doctoral thesis "Lu Xun on Display: Memory, Space and Media in the Making of World Literary Heritage or Th...
Gesehen am 28.02.2023
Keywords: Forschungsdaten; Datenbank